Pelatihan Teknik APA STYLE Bagi Mahasiswa Asal Kawasan Teluk Ampimoi Di Kota Jayapura Provinsi Papua - Dolfina Costansah Koirewoa; Edoward Raunsay (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
Writing academically not only requires a good understanding but also needs to be trained or accustomed to starting from doing college assignments to making a final writing or thesis for a student. A student in daily lectures has been faced with various scientific writings where each of these writings requires or goes through scientific stages and must be presented logically, according to facts and most importantly must also be systematic. Display systematically requires media or computer/laptop technology devices. Based on the observation that the use of laptop/computer media in making scientific writings is rarely maximized by students, even though computer equipment has been equipped with tools that are very helpful for students/writers. This training activity is very useful in improving the ability of students at the final level in preparing thesis. The service activity of implementing the APA Style system for Students from Ampimoi Bay, Yapen Islands Regency at Several Universities in Jayapura the Education City.